Dampak Penyelenggaraan Event Olahraga Terhadap Tingkat Kesejahteraan Masyarakat Di Desa Montong Ajan, Kecamatan Praya Barat Daya, Kababupaten Lombok Tengah - Fahmi, Saiful; Yudha Isnaini, Lalu Moh; Anam, Khaerul (Universitas Hamzanwadi, 2024)
This study aims to examine the impact of organizing sports events on the level of community welfare. This research uses a qualitative descriptive approach, with the subject of the Montong Ajan village community who live around the place where sports event activities are held including the people of Montong Ajan, Batun Dace, and Torok Aik Belek hamlets, who utilize the sports event activities. Data collection techniques are carried out by interview, observation, and documentation. Data analysis techniques use qualitative analysis of interactive models with data reduction, data presentation, and conclusion drawing. The results of this study are that not all people in Montong Ajan village get an impact on the implementation of a sports event on their welfare, only some people get an impact from the existence of these sports event activities, namely people who live around the sports event activities and who take advantage of the event to open a business, the community gets an impact on their welfare so that they are able to meet their needs through the income from each organized sports event. The conclusion is that only a few people get the impact of the event.